Uncovering lupus nephritis-specific genes and the potential of TNFRSF17-targeted immunotherapy: a high-throughput sequencing study - Zou, Xiaojuan; Yang, Mingyue; Ye, Zhuang; Li, Tie; Jiang, Zhenyu; Xia, Ying; Tan, Shenghai; Long, Yu; Wang, Xiaosong (Frontiers in Immunology, 2024)
In this study, we sought to identify lupus nephritis (LN) specific genes and potential therapeutic targets. We performed high-throughput transcriptome sequencing on peripheral blood mononuclear cells (PBMCs) from LN patients, using healthy individuals and systemic lupus erythematosus (SLE) patients without LN as controls.This analysis revealed 1493 and 205 differential genes in the LN group compared to the control and SLE without LN groups respectively, with 70 genes common to both sets, marking them as LN-specific. These LN-specific genes were significantly enriched in the 'regulation of biological quality' GO term and the cell cycle pathway.Validation of sequencing results was achieved through qRT-PCR for 5 upregulated and 5 downregulated genes. Notably, several genes including TNFRSF17 were significantly overexpressed in the kidneys of both LN patients and NZB/W mice.TNFRSF17 levels correlated positively with urinary protein levels, and negatively with complement c3 and c4 levels in LN patients. Furthermore, the TNFRSF17targeting drug IBI379 effectively induced apoptosis in patient plasma cells without significantly affecting B cells. These findings suggest that TNFRSF17 could serve as a potential therapeutic target for LN, with IBI379 presenting as a promising treatment option.